Urban dynamics and transcultural communication in medieval Sicily - Jäckh, Theresa; Kirsch, Mona (Verlag Ferdinand Schöningh, 2017)
At the heart of the Mediterranean, the island of Sicily has long been a place of encounter. Witness to conquests and cycles of migration, the island’s enviable position as a unique nexus of exchange has left it heir to a rich linguistic, religious, ethnic and cultural inheritance. As the island’s primary conduits of interaction, Sicily’s vibrant cities not only functioned as important hubs for the exchange of goods and knowledge, but also facilitated the transcultural contact of peoples and cultures. This volume offers multi-disciplinary approaches in endeavouring to investigate how such manifold influences shaped the cities of the island and were reflected in the urban dynamics and transcultural communication of medieval Sicily.
Keywords: Konferenzschrift -- 2015 -- Heidelberg; Geschichte 1000-1500; Handel; Migration; Kommunikation; Kulturaustausch; Kulturkontakt; Stadt; Sizilien